World Health Organization (WHO)/International Society of Urological Pathology (ISUP) grading in fine‐needle aspiration biopsies of renal masses. Issue 11 (29th November 2018) - Perrino, Carmen M.; Cramer, Harvey M.; Chen, Shaoxiong; Idrees, Muhammad T.; Wu, Howard H.
Abstract : Background: Utilization of fine‐needle aspiration (FNA) biopsy for the evaluation of renal masses has been increasing at our institution. At times diagnostic material on direct smears is superior to that in the cell block/core biopsy, therefore assigning an accurate nuclear grade in the cytopathology report would provide useful prognostic information. Methods: Search of the pathology database identified renal FNAs performed during an 11‐year period (2006–2017). Corresponding core biopsies and resections were identified. Cases with a diagnosis of primary renal neoplasia on FNA, core biopsy, and/or resection were included. Two pathologists reviewed all cases and assigned a World Health Organization (WHO)/International Society of Urological Pathology (ISUP) grade to each FNA, core biopsy, and resection case. Results: A total of 162 kidney FNAs were identified. Primary renal neoplasia was diagnosed in 137 cases on core biopsy/resection. Among diagnostic FNAs of clear cell RCC and papillary RCC with core biopsy/resection specimens for re‐review ( n  = 52), reviewers assigned a concordant WHO/ISUP grade to 83% (43/52) of cases. Among 9 cases with discrepant scores, all had a discrepancy of 1 grade and were undergraded on FNA. Using a two tier grading system (low vs. high grade), reviewers assigned a concordant grade to 88% (46/52) of cases. Among 6 cases with discrepant scores, all were classified as low grade (WHO/ISUP grade 2) on FNA versus high grade (WHO/ISUP grade 3) on resection. Conclusion: The WHO/ISUP grade assigned on FNA shows good concordance with subsequent resection/core specimens (83%), with all discrepant cases being undergraded by one grade.